Analisis Pemakaian dan Sistem Distribusi Air Bersih PDAM - Abdurrafiq, Abdurrafiq; Endang Pudji Widjajati (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
This journal discusses the analysis of the use and distribution system of clean water at PDAM Tirtajati, Cirebon City. Water distribution experiences inequality between regions and regions, while water demand continues to increase due to population and economic growth which requires water supplies. This research uses quantitative descriptive methods using primary and secondary data. The results of the research show that the need for clean water continues to increase from 2022 to 2040. The volume of water needed reaches 4,459,295.52 m3 in 2022, increasing to 4,758,068.32 m3/year/person in 2040. The results of the analysis show that PDAM service coverage up to In 2040 it will only reach 62.17%. The clean water distribution system at PDAM Tirtajati relies on the principle of gravity. Based on the results of this research, several things can be recommended that can improve services at PDAM Tirtajati, one of which is increasing the PDAM's water production capacity to anticipate an increase in the community's clean water needs in the future as well as carrying out regular maintenance and repairs to the PDAM distribution network to reduce losses. water.